Comparison of growth and nutritional evolution stages in infants with working mothers and infants with housewife mothers in Isfahan - Shams, Behzad (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Studies have shown that the growth status of the children with working mothers is about 2 standard deviations lower than that of the children of housewife mothers. It seems that absence of mothers in the second stage of nutritional evolution (attachment), which is a very sensitive stage, has an important role in initiating and continuation of an appropriate supplemental feeding. MATERIALS AND METHODS: In this cross-sectional study, 50 children of working mothers and 50 children of housewife mothers were selected by non-probable consecutive sampling method. Growth charts of the children in the two studied groups were assessed within seven age groups. Knowledge and attitude of the mothers regarding nutritional evolution stages in the two studied groups were assessed Obtained data were analyzed using Software SPSS18 and statistical tests such as chi-square, t-test, and Mann–Whitney test. RESULTS: Growth monitoring charts of the infants with housewife mothers were better than those of infants with working mothers in three out of seven age groups (12–18, 18–24, and 24–30 months) (P=0.02). Mean of knowledge and performance of the mothers about nutritional evolution stages was not significant in the two studied groups (P>0.05). CONCLUSION: This study showed that growth status of children with housewife mothers in their second year of life was better than that of children with working mothers. Awareness and knowledge of the mothers about nutritional evolution stages and education of mothers about appropriate behaviors in each stage helped them to recognize the children's needs and did their best for their children.